2022
DOI: 10.1002/ecs2.4334
|View full text |Cite
|
Sign up to set email alerts
|

Grassland productivity responds unexpectedly to dynamic light and soil water environments induced by photovoltaic arrays

Abstract: Agrivoltaic (AV) systems are designed to coproduce photovoltaic (PV) energy on lands simultaneously supporting agriculture (food/forage production). PV infrastructure in agroecosystems alters resources critical for plant growth, and water‐limited agroecosystems such as grasslands are likely to be particularly sensitive to the unique spatial and temporal patterns of incident sunlight and soil water inherent within AV systems. However, the impact of resource alteration on forage production, the primary ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…At cooler, wetter Aurora, CO the model predicts no beneficial shading effects. Intriguingly, recent results from a nearby site showed that grasses growing beneath a photovoltaic array exhibited higher growth in regions receiving morning sun and afternoon shade despite having lower average soil moisture content than regions with morning shade and afternoon sun (Sturchio et al 2023). These experimental results suggest that (1) plants may acclimatize to agrivoltaic shading or (2) that the benefits of afternoon agrivoltaic shading may be more pronounced when crops experience water restriction.…”
Section: Discussionmentioning
confidence: 67%
“…At cooler, wetter Aurora, CO the model predicts no beneficial shading effects. Intriguingly, recent results from a nearby site showed that grasses growing beneath a photovoltaic array exhibited higher growth in regions receiving morning sun and afternoon shade despite having lower average soil moisture content than regions with morning shade and afternoon sun (Sturchio et al 2023). These experimental results suggest that (1) plants may acclimatize to agrivoltaic shading or (2) that the benefits of afternoon agrivoltaic shading may be more pronounced when crops experience water restriction.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, on sites with very short stature (or an absence of) autochthonous vegetation and animals, typical of dry, sunny rangelands of the world, LoCoAgri-PV and LoCoEco-PV might indeed be quite appropriate options, as the shade from a high concentration of PV may be beneficial to the vegetation and animals. On several sites in temperate and arid regions, researchers have noted improved vegetation health and yield improvements on low-cost agri-and eco-PV arrays without increases in spacing from mainstream LoCoPV (Sturchio et al, 2022). This point is again examined in Section 4.2.…”
Section: Lowest-cost Agrivoltaicsmentioning
confidence: 93%
“…The total displaced water use was 8 times the O&M use for those arrays, thus installing solar PV in water scarce regions has significant potential to reduce water use, which bolsters findings from previous studies [63][64][65][66][67][68] . This analysis does not incorporate the additional hydrologic effects of modifying surface energy and water budgets, including reducing evapotranspiration and the potential for increased groundwater recharge 22,[69][70][71][72][73][74] .…”
Section: The Potential For Water Sustainability With Agrisolar Co-loc...mentioning
confidence: 99%